Snow in the Tropics : A History of the Independent Reefer Operators (2019)
Snow in the Tropics offers the first comprehensive history of the independent reefer operators, companies that are dedicated to transport refrigerated products by ship, from the early 20th century to the present. Readership: All interested in maritime history, particularly those with an interest in the modern history of the shipping industry.